Transformando a Presença Feminina em Computação a partir de Oficinas de Programação em Python - Coutinho, Fernanda dos Santos; Junqueira e Silva, Ana Carolina; Velten, Hanna Bomfim; Oliveira, Raphaela Rita de Souza; Dias, Lara da Silva; Valle, Pedro Henrique Dias; Oliveira, Alessandreia Marta de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Female participation in Computing continues to face historical barriers of inequality and underrepresentation. Educational outreach initiatives play a strategic role in promoting equity and fostering the inclusion of girls and women in the field. This work reports on a project offering introductory Python programming workshops for high school students and graduates, using active learning methodologies, accessible materials, and multimedia resources. The aim was to spark interest in Computing, strengthen self-confidence, and deconstruct stereotypes. Results indicate greater engagement, improved understanding of programming concepts, and increased protagonism in learning processes. Aligned with the United Nations Sustainable Development Goals (SDGs), this initiative reinforces the social and academic relevance of outreach actions for cultural transformation and the expansion of female presence in Computing, addressing a gap in the literature by demonstrating the effectiveness of Python-focused workshops for this specific audience.